APLIKASI POMPA AIR TENAGA SURYA PADA SMKN 1 CIMAHI - Sri Paryanto Mursid (Jurnal Difusi, 2021)
The use of abundant solar energy in Indonesia concerns the government, especially for regions that are still not electrified by the PLN cable network. The conversion of solar energy into electrical energy carries out using PV solar panels to form a solar power plant (PLTS). The existence of PLTS is increasing in number so that competent human resources are needed to manage and operate it. With this awareness, the Community Service Activities Program of the Bandung State Polytechnic, Energy Conversion Engineering Department invites partnerships at SMKN1 Cimahi to jointly equip students to get provision for PLTS competencies. The competency developed is more specifically in the use of solar-powered water pumps. This activity was held when the very dangerous Covid19 virus pandemic forced us to work from home (WFH). However, instead of being an obstacle, it gives a result that should be appreciated, namely gaining experience in developing practical learning modules that can be delivered online. Analysis of the PKM implementation results proves that implementing the practice with the tool module can be held online.